BULBOPHYLLUM ACEHENSE (ORCHIDACEAE), A NEW SPECIES OF SECTION BECCARIANA FROM ACEH, SUMATRA, INDONESIA - Destario Metusala (Universitas Mataram, 2020)
Abstract: Sumatra island has been considered as one of the diversity centers for Bulbophyllum species in Indonesia. During botanical exploration held in the mid of 2019, specimens of the genus Bulbophyllum (Orchidaceae) section Beccariana have been collected from highland forests in Aceh Province, Sumatra, Indonesia. Their flower morphology and plant habitus are relatively close to Bulbophyllum cornutum (Blume) Rchb.f. (section Beccariana). Therefore, the aim of this research is to compare the Bulbophyllum sp. from Aceh with closely resemble species in section Beccariana, also to describe and illustrate the morphological characteristics of this Bulbophyllum species from Aceh. Morphological description was carried out by characterizing the flowers and plant habit of the living plants, spirit materials, dried herbarium specimens and photographs. Morphological comparisons with other closely resemble Bulbophyllum species were carried out based on data from protologue, living plants, herbarium specimens and several taxonomic references. The result based on morphological comparisons has showed there were several distinct differences on their flower characteristics, especially on the labellum. Therefore, this Bulbophyllum sp. from Aceh is here described and illustrated as new species, namely Bulbophyllum acehense.Keywords: Bulbophyllum, Sumatra, OrchidaceaeÃÂ